1994
DOI: 10.1177/002199839402800705
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fiber Architecture Parameters on Deformation Fields and Elastic Moduli of 2-D Braided Composites

Abstract: The effects of various braiding parameters for 2-D triaxially braided textile composites were systematically investigated both experimentally and analytically. Four different fiber architectures designed to provide a direct comparison of the effects of braid angle, yarn size and axial yarn content were tested. Moiré interferometry was employed to study the effect of these parameters on the surface strain fields in the material. Moiré results for the surface strain fields were found to be strongly influenced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(70 citation statements)
references
References 3 publications
1
68
0
1
Order By: Relevance
“…Under uniaxial static load, an increase in braid angle leads to a decrease in the longitudinal modulus and an increase in transverse modulus. In addition, the shear modulus and the in-plane Poisson's ratio increase with an increase in braid angle with a maximum peak at ±45 • [19]. The transverse moduli, strength, and dimensional stability of braided composites arise from helical fibres and the damage tolerance results from the locking mechanism between the intertwined fibres of the braid architecture that helps in preventing or limiting the yarn delamination [2].…”
Section: Braided Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Under uniaxial static load, an increase in braid angle leads to a decrease in the longitudinal modulus and an increase in transverse modulus. In addition, the shear modulus and the in-plane Poisson's ratio increase with an increase in braid angle with a maximum peak at ±45 • [19]. The transverse moduli, strength, and dimensional stability of braided composites arise from helical fibres and the damage tolerance results from the locking mechanism between the intertwined fibres of the braid architecture that helps in preventing or limiting the yarn delamination [2].…”
Section: Braided Compositesmentioning
confidence: 99%
“…19 Representative images of burst filament wound tubes of all reinforcement angles Table 3 illustrates the estimated fibre volume fraction for each wind angle along with the density of the composite. The density and elastic properties of a unidirectional fibre reinforced ply at a specific fibre volume fraction (f ) were calculated through the HalpinTsai equations.…”
Section: ˚55˚65˚87˚87/70/87fmentioning
confidence: 99%
“…The fiber bundles of the large tow composites used by automotive industry typically contain on the order of 1Ok filaments. (Naik et al, 1994) Figure 2.2 shows two sectional micrographs of a multi-ply braided composite laminate (Dadkhah et al, 1995). It can observed that the fiber geometry exhibits many irregular features that are difficult to model.…”
Section: Physical Description Of Braided Compositementioning
confidence: 99%
“…This required that the diameter of the axial braider, d,, be larger than that of the 4, braiders db,. Their ratio was: 5 = case da (b) (1) (Naik et al, 1994), and (d) cross sectional micrographs along the axial and f8 braiders (Dadkhah et al, 1995). Also, the model only incorporated the undulation of the +0 braiders, and the lenticular cross section of the braiders were simplified to be rectangular to preserve the flattened and expansive characteristic of the fiber tows.…”
Section: Simplified Geometric Modelmentioning
confidence: 99%
See 1 more Smart Citation